Error perception in gymnastics: two consecutive interventions - Jeraj, D. (Science of Gymnastics Journal, 2016)
The coach`s perception of movement errors is crucial for the feedback. Two consecutive studies investigated exploratory the influence of transfer of knowledge (study 1; S1) and the influence of motor experience (study 2; S2) on error perception rate of the gymnastics element handstand with a roll. Participants of S1 (n = 18) and S2 (n = 21) are distributed to either a control or an intervention condition. The error perception rate of a video test was used as the dependent variable. Interventions consisted of 180 minutes transfer of knowledge sessions (S1) and 90 executions of handstand with a roll (S2). The mental structure (S1) and an execution protocol with subjective performance are used for monitoring. The error perception rate increased significantly for all conditions. An influence of transfer of knowledge and motor experience was not found. A systematic change in the mental structure on the descriptive level and a subjective improvement of the handstand performance was found. The overall increase of the error perception rate is seen as a learning effect. It remains unclear whether there are long term effects on error perception and to what extent changes of mental structure and subjective performance can be used for the feedback.